1) dy/dx = x-1+xy-y 2) (x+y)power2dy/dx=1 3) xdy/dx=y(logy-logx+1) 4) dy/dx=log(x+1)

Asked by Archana | 10th Oct, 2013, 03:39: AM

Expert Answer:

Please ask one question at a time. The solution to your first question is as follows:
 
dy/dx = x-1+xy-y
dy/dx = (x-1)+y(x-1)
dy/dx = (x-1)(1+y)
dy/(1+y) = (x-1) dx
log(1+y) = x^2/2 - x + c
1+y = e^(x^2/2 - x). e^c
y = e^(x^2/2 - x). C - 1

Answered by  | 10th Oct, 2013, 09:17: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.